Modeling of Cavitating Flow through Waterjet Propulsors - Jules W. Lindau; Christopher Pena; Warren J. Baker; James J. Dreyer; William L. Moody; Robert F. Kunz; Eric G. Paterson (International Journal of Rotating Machinery)
A computational-fluid-dynamics-based modeling effort to capture flow through an axial flow waterjet propulsor is presented. The effort covered the waterjet flow over a wide range of flow coefficients and into cavitation-driven breakdown. The computations are presented in cavitation at two values of flow coefficient through a series of decreasing operating inlet total pressure. The computational results are compared to experimental measurements. Suction-surface and tip-gap cavitation patterns are presented and compared to experimental photographs. Presented computational solutions are blade-passage steady and periodic. The computational results apply a powering iteration methodology to facilitate coupling of rotor, stator, and inflow and outflow ducting.